Autoavaliação institucional : significados e efeitos sobre as políticas educacionais na Universidade Federal da Paraíba - Cavalcanti, Lourdes Maria Rodrigues (2024)
The objective of this thesis was to identify the meanings arising from the results of the Institutional Self-Assessment Reports, relating to the years 2021, 2022 and 2023, issued by the UFPB's own Assessment Committee, according to the criteria of the Institutional Assessment Instrument of the National Higher Education Assessment System (SINAES), and what effects favored the advancement of educational policies conducted by the Federal University of Paraíba (UFPB). Such Reports constituted the sample of this research. Institutional documents were used as primary sources (Institutional Development Plan for the five-year period 2019/2022 and the Institutional Management Report for the year 2023), as well as those referring to current legislation, specific to the SINAES Institutional Assessment Instrument, Laws and regulations intrinsic to the evaluation of higher education, among others. It was qualitative research, of an applied, descriptive nature, in terms of objectives, with a bibliographicdocumentary strategy, characterized as documentary analysis, using, for data processing, the IRaMuTeq software – based on Salviati (2017) – as support for data processing to perform textual analysis, Reinert analysis, Descent Hierarchical Classification Dendrogram and Word Cloud. The results of this research stand out: in relation to the PDI UFPB/2019/2023, the need to implement actions aimed at building a culture of institutional planning was noted. The following 5w2h Plans were prepared, according to the respective Institutional Self-Assessment Reports: i) Institutional Self- Assessment Report for the year 2021, Axis III – Academic Policies – aiming to develop actions aimed at mitigating communication difficulties between UFPB and internal and external communities; ii) Institutional Self-Assessment Report, for the year 2022, Axis II – Institutional Development – the available data was insufficient to carry out analyses; however, in relation to Axis IV – Management Policies, a 5w2h Plan was suggested aiming at the development of actions aimed at establishing measurable goals, through institutionalized performance indicators. The 5w2h Plan - applied to the Indicators "Teacher Training Policy" and "Administrative Technical Training Policy", from Axis IV – Management Policies, suggested the same action, for both indicators: institutionalize the internationalization of training policy, for both segments; iii) 2023 Institutional Self- Assessment Report, Axis V – Infrastructure: the 5w2h Plan proposed actions to be developed by the Infrastructure Superintendence and the UFPB Dean of Planning. Regarding the meanings of the Institutional Self-Assessment Reports, as institutional learning, progress was noted in relation to organizational planning, as the CPA/UFPB improved the Institutional Self-Assessment Instruments during the period researched. As effects, through the analysis of the 2023 Institutional Management Report, it was found that objectivity and transparency relating to Risk Management, Governance, Strategy and Institutional Performance, and relating to UFPB's Budgetary, Financial and Accounting Management. Furthermore, 5w2h plans are suitable to the political, academic and management adjustments necessary to improve SINAES indicators, which are necessary to improve teaching, research and extension, within the scope of UFPB.